The Cypriot Generation of the Poets of the Invasion - Ziras, Alexis (Études helléniques / Hellenic Studies, 2007)
In this article, Alexis Ziras focuses on the Cypriot generation of poets of the invasion. He refers to the historic tragedy of 1974 when Turkey invaded Cyprus, and its impact on Cypriot poetry. He also looks at the linguistic and stylistic characteristics.